Time-to-treatment initiation of colchicine and cardiovascular outcomes after myocardial infarction in the Colchicine Cardiovascular Outcomes Trial (COLCOT). (29th August 2020) - Bouabdallaoui, Nadia; Tardif, Jean-Claude; Waters, David D; Pinto, Fausto J; Maggioni, Aldo P; Diaz, Rafael; Berry, Colin; Koenig, Wolfgang; Lopez-Sendon, Jose; Gamra, Habib; Kiwan, Ghassan S; Blondeau, Lucie; et al.
Abstract: Aims: The COLchicine Cardiovascular Outcomes Trial (COLCOT) demonstrated the benefits of targeting inflammation after myocardial infarction (MI). We aimed to determine whether time-to-treatment initiation (TTI) influences the beneficial impact of colchicine. Methods and results: In COLCOT, patients were randomly assigned to receive colchicine or placebo within 30 days post-MI. Time-to-treatment initiation was defined as the length of time between the index MI and the initiation of study medication. The primary efficacy endpoint was a composite of cardiovascular death, resuscitated cardiac arrest, MI, stroke, or urgent hospitalization for angina requiring coronary revascularization. The relationship between endpoints and various TTI (< 3, 4–7 and > 8 days) was examined using multivariable Cox regression models. Amongst the 4661 patients included in this analysis, there were 1193, 720, and 2748 patients, respectively, in the three TTI strata. After a median follow-up of 22.7 months, there was a significant reduction in the incidence of the primary endpoint for patients in whom colchicine was initiated < Day 3 compared with placebo [hazard ratios (HR) = 0.52, 95% confidence intervals (CI) 0.32–0.84], in contrast to patients in whom colchicine was initiated between Days 4 and 7 (HR = 0.96, 95% CI 0.53–1.75) or > Day 8 (HR = 0.82, 95% CI 0.61–1.11). The beneficial effects of early initiation of colchicine were also demonstrated for urgent hospitalization for angina requiring revascularization (HR = 0.35), all coronary revascularization (HR = 0.63), and the composite of cardiovascular death, resuscitated cardiac arrest, MI, or stroke (HR = 0.55, all P < 0.05). Conclusion: Patients benefit from early, in-hospital initiation of colchicine after MI. Trial Registration: COLCOT ClinicalTrials.gov number, NCT02551094. Graphical Abstract: